Tea Import Policy Recommendation - Salam, Aziza Rahmaniar (Research Institute for Tea and Cinchona, 2014)
This paper analyzes a posibility of a proposed policy on the importation of tea that can increase performance and competitiveness of Indonesia tea. The method used was prosÂpective analysis method. The analysis revealed that the proposed policy is to increase import duty tariffs and non-tariff barriers. Policies proposed on non-tariff barriers are import controls by constructive a regulation on proÂduct importer, Indonesian packaging label, and certain importers for importation of tea as an ingredient and formulation on technical verification (VPTI) for all importation of tea products containing specified information in maximum crude fiber content of 15% and minimum of 33% extract in water (w/w) as indicated in SNI.